El control interno contable de inventarios y su aporte a la razonabilidad de los estados financieros de la empresa Grupo R&R - Camacho Gavilanes, Diana Carolina (2015)
Internal control is essential in the area of inventories to ensure reliability in commercial transactions made in business, being essential to have a manual of internal accounting control of inventories to avoid the risks of fraud. This paper aims to serve as a guide in inventory control in the company " R & R GROUP " whose business is the sale of farm inputs. The manual of policies and procedures developed it based on the need for the company to control inventories, processes being designed to improve the record of the movement of stocks by applying the NIC 2 "Inventories and Internal Control" COSO " where clear and concise rules specified apply to the valuation of its inventory .